The philosophy of A. Bergson in a critical assessment by G. V. Plekhanov - Kulak, Nikita I. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article discusses the main ideas of A. Bergson in the assessment of one of the main representatives of Russian philosophy in the second half of the 19th – early 20th centuries G. V. Plekhanov. The specificity of the main provisions of A. Bergson is revealed through the critical analysis and substantiation from the standpoint of historical materialism of G. V. Plekhanov. The significance of A. Bergson’s intuitivism in the development of the philosophical doctrines of Russian and Western European thinkers is shown. The materialistic trends in the philosophy of A. Bergson are analyzed.
Keywords: G. V. Plekhanov; A. Bergson; creative evolution; historical materialism